Workplace bullying and presenteeism: the path through emotional exhaustion and psychological wellbeing - Neto, M.; Ferreira, A. I.; Martinez, L. F.; Ferreira, P. C. (Annals of Work Exposures and Health, 2017)
Objective: Workplace bullying is an increasing phenomenon that concerns managers and employees. However, few studies have investigated how workplace bullying relates with work-related exhaustion and indicators of productivity loss due to presenteeism. Thus, the aim of the present study was to examine the intervening variables of emotional exhaustion and psychological wellbeing in the direct and indirect relationships between workplace bullying and indicators of productivity loss due to presenteeism. Method: In a cross-sectional study, we tested a structural equation model using web survey data of 353 workers from a service company, with the variables: workplace bullying (Quine, 1999), emotional exhaustion (Maslach Burnout Inventory; MBI), psychological wellbeing (GHQ-28), and indicators of productivity loss due to presenteeism (SPS-6). All variables presented acceptable psychometric evidence. Results: The final model revealed a reasonable fit. Workplace bullying was significantly and positively related to emotional exhaustion, which in turn, was significantly related to the loss of psychological wellbeing. Workplace bullying, emotional exhaustion, and the loss of psychological wellbeing were negatively related to concentration (avoiding distraction). Emotional exhaustion and psychological wellbeing mediated the studied structural relationships. Conclusions: Our study contributes to theory and practice, since occupational health professionals should be aware that burnout and the loss of wellbeing may be related to workplace bullying and that productivity loss due to presenteeism may be a warning sign. Leaders can understand the underlying mechanism that explains employees’ productivity loss due to presenteeism by addressing workplace bullying and its negative relation with emotional exhaustion and wellbeing.